Restorative Dental Care and CO V ID -19 Pandemic: Reviewing the Treatment Guidelines and Evaluating Patients' Opinion Qualitatively in a Nigerian Tertiary Hospital. (2020)
Objectives: The study aimed at reviewing the different measures and strategies put in place globally to ensure successful management of restorative dental patients during the COVID-19 era and to evaluate the knowledge and information on patients' opinion on the impact of the pandemic on their restorative care through a qualitative study design. Methodology: Search for articles on guidelines for restorative care through PUBMED using the keywords COVID-19, guidelines, protocols and restorative care was done. About 42 related articles were downloaded and appraised for necessary information as regards standard protocols in restorative care. The qualitative study involved individual interview of randomly selected 15 patients seeking restorative care that consented to participate in the study. The audiotaped interviews were transcribed verbatim and thematic analysis of data generated was done. Four themes were identified from the data and these included knowledge about COVID-19, view about the infection and infection control, the effects of the lockdown on treatment as well as the fear about contracting the disease. Result: Standard guidelines for different phases (pre, intra and post treatment) were carefully outlined. Fifteen patients, 8 females and 7 males between ages 19 and 72 years with mean age of 39.6 ±17.53 years were interviewed. All the patients had knowledge about COVID-19 infection but the majority were not familiar with the relationship between dentistry and spread of the infection. Repeated visits to dental clinic without being attended to, during the lockdown resulted in patients using self-medication. The fear of contracting the infection in dental clinic was low among the participants and the few that had the fear were those that showed good knowledge about the risk of contracting COVID-19 infection through restorative care. Conclusion: Strict adherence to standard protocols and guidelines should always be followed even after COVID-19 pandemic to ensure continual confidence of patients in the clinicians.